Standard-Compliant Multiple Description Video Coding over Packet Loss Network. (22nd April 2010) - Bai, Huihui; Zhao, Yao; Zhang, Mengmeng
Abstract : An effective scheme of multiple description video coding is proposed for transmission over packet loss network. Using priority encoding transmission, we attempt to overcome the limitation of specific scalable video codec and apply FEC-based multiple description to a common video coder, such as the standard H.264. Firstly, multiple descriptions can be generated using temporal downsampling and the frame with high motion changing is duplicated in each description. Then according to different motion characteristics between frames, each description can be divided into several messages, so in each message better temporal correlation can be maintained for better estimation when information losses occur. Based on priority encoding transmission, unequal protections are assigned in each message. Furthermore, the priority is designed in view of packet loss rate of channels and the significance of bit streams. Experimental results validate the effectiveness of the proposed scheme with better performance than the equal protection scheme and other state-of-the-art methods.